Misleading concepts about mysterious zero - Azram, Mohammad (International Association of Computer Science and Information Technology Press (IACSIT), 2015)
Abstract: Zero was a brilliant innovation and most significant achievement but it has threatened the foundations of modern physics and is behind all of the big puzzles in physics. Today, zero lies at the heart of one of the biggest scientific controversies of all time. The mysterious zero is posing challenges not only to intellectuals, philosophers, scientists, mathematicians, historians and theologizes but also is confusing and un-easing a common man. This article is devoted to raise awareness of social, conceptual and operational issues related with mysterious zero. The focus is those individuals involved in the process of teaching and learning mathematics. It is suspected that this article will enable them to think more clearly rather than to be in a state of confusion.